1995
DOI: 10.1007/978-3-662-03088-2
|View full text |Cite
|
Sign up to set email alerts
|

Scheduling Algorithms

Abstract: PrefaceThis is a book about scheduling algorithms. The first such algorithms were formulated in the mid fifties. Since then there has been a growing interest in scheduling. During the seventies, computer scientists discovered scheduling as a tool for improving the performance of computer systems. Furthermore, scheduling problems have been investigated and classified with respect to their computational complexity. During the last few years, new and interesting scheduling problems have been formulated in connect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
370
0
2

Year Published

1999
1999
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 358 publications
(372 citation statements)
references
References 39 publications
0
370
0
2
Order By: Relevance
“…Therefore, the parallel performance of the ex- plicit scheme is expected to be dominated by the load balance. Another key issue of communication is scheduling [2]. In Alya, a relatively simple but efficient scheme is used, based on coloring and build upon the adjacency graph of each subdomain.…”
Section: Communication Types and Schedulingmentioning
confidence: 99%
“…Therefore, the parallel performance of the ex- plicit scheme is expected to be dominated by the load balance. Another key issue of communication is scheduling [2]. In Alya, a relatively simple but efficient scheme is used, based on coloring and build upon the adjacency graph of each subdomain.…”
Section: Communication Types and Schedulingmentioning
confidence: 99%
“…Problem Statement Job scheduling on parallel machines has been widely studied (see, e.g., the surveys in [4], [28]). In particular, much attention was given to interval scheduling [19], where jobs are given as intervals on the real line, each representing the time interval during which a job should be processed; each job has to be processed on some machine, and it is commonly assumed that a machine can process a single job at any given time.…”
Section: Introductionmentioning
confidence: 99%
“…All the jobs in the batch start simultaneously, and the completion time of a batch is the last completion time of any job in the batch. (For known results on batch scheduling, see, e.g., [4].) Our scheduling problem differs from batch scheduling in several aspects.…”
Section: Introductionmentioning
confidence: 99%
“…• shown that the problem of scheduling wrapped core tests on the TAM is equivalent to independent job scheduling on identical machines, • made use of a preemptive approach to produce a solution with optimal test time in linear time [2] using reconfigurable wrappers [15], and • extended the scheduling algorithm to handle wrapped core tests and cross-core tests while preserving the production of an optimal solution in linear time.…”
Section: Introductionmentioning
confidence: 99%
“…4 we present our optimal preemptive test scheduling technique, based on a known preemptive scheduling algorithm [2]. In the experiments we have made a comparison with previous approaches and we illustrate the advantages with our wrapper and its use in the proposed scheduling approach in Section 5.…”
Section: Introductionmentioning
confidence: 99%